(untitled) (Asian Journal of Medical Sciences, 2017)
Background: Coronary artery disease (CAD) is the major disease leading to cause mortality and morbidity. The imbalance between the generation of reactive oxygen species (ROS) and the intrinsic antioxidant defense system leading to the oxidative stress, has been implicated in the pathogenesis of the cardiovascular disease. The formed free radicals and subsequent lipid peroxidation may be responsible for myocardial damage in patients undergoing percutaneous coronary interventions. Therefore, the understanding of the pathophysiological role of ROS generated during or after coronary interventions is essential to improve the success rate of these procedures. Aims and Objective: The aim of this study was to evaluate the time course changes of oxidant and antioxidant status, in patients undergoing percutaneous coronary interventions (PCI). Materials and Methods: The study included 120 consecutive patients (117 males, 3 females; mean age 58.4 years) who underwent elective PCI. Coronary angiography and coronary angioplasty were performed according to the standard protocols. Blood samples were taken just before (0hrs) and at 4 hrs and 24 hrs after coronary interventions to determine the oxidative status i.e. plasma malondialdehyde (MDA) and for antioxidative status, erythrocyte glutathione peroxidase (GPx), erythrocyte glutathione (GSH) and plasma ferric reducing ability of plasma (FRAP). Results: There was significant increase in MDA levels (1.87±0.34, 1.90±0.46, p=0.000), at 4hrs and 24hrs after coronary interventions when compared to baseline levels. After coronary interventions, the GPx activity (12.96±8.37, 12.3±7.76, p=0.000) and FRAP levels (0.73±0.21, 0.70±0.23, p=0.001 respectively) were found to be increased significantly at 4hrs and 24hrs. However, the glutathione levels (2.40±0.57, 2.47±0.53, p=0.040) were decreased at 4hrs and 24hrs after coronary interventions. Conclusion: Our study demonstrates that presence of oxidative stress in coronary interventions. The increase in antioxidants in the present study may be due to paradoxical increase in oxidant levels in patients undergoing coronary interventions. Asian Journal of Medical Sciences Vol.8(2) 2017 29-33